Convergence of interoception, emotion, and social cognition: A twofold fMRI meta-analysis and lesion approach. (March 2017) - Adolfi, Federico; Couto, Blas; Richter, Fabian; Decety, Jean; Lopez, Jessica; Sigman, Mariano; Manes, Facundo; Ibáñez, Agustín
Abstract: Guided by indirect evidence, recent approaches propose a tripartite crosstalk among interoceptive signaling, emotional regulation, and low-level social cognition. Here we examined the neurocognitive convergence of such domains. First, we performed three meta-analyses of functional magnetic resonance imaging studies to identify which areas are consistently coactivated by these three systems. Multi-level Kernel Density Analysis (MKDA) revealed major overlaps in the right anterior insular and frontotemporal regions (viz., the orbitofrontal and inferior frontal gyri, the amygdala, and mid temporal lobe/subcortical structures). Second, we explored such domains in patients with fronto-insulo-temporal damage. Relative to controls, the patients showed behavioral impairments of interoception, emotional processing, and social cognition, with preservation of other cognitive functions. Convergent results from both studies offer direct support for a model of insular-frontotemporal regions integrating interoception, emotion, and social cognition.